FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI DI BALAI KOTA SURAKARTA - Nadhia Ratna Puspaningrum; Muhammad Hasan Ma'ruf; Johny Subarkah (ITB AAS INDONESIA, 2022)
This study aims to determine the effect of User Participation, Training, and Involvement on Accounting Information System Performance (Case study at Surakarta City Hall). This study uses quantitative research with primary data with data collection techniques using questionnaires. The population in this study were all Surakarta City Hall employees, totaling 5000 employees. The sampling technique used in this research is purposive sampling drawn 80 samples as respondents. The data analysis used to process the data in this research is descriptive statistical analysis, validity test, reliability test, classical assumption test using normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing using multiple linear regression analysis, F test, t test, and test the coefficient of determination (R2). The results of data processing using SPSS show that simultaneously, participation, training, and user involvement have a significant effect on the performance of accounting information systems. Then partially participation has a positive and significant effect on the performance of accounting information systems. Training has a positive and significant effect on the performance of accounting information systems partially. User involvement has a positive and significant effect on the performance of accounting information systems partially